Exploring Alcohol Consumption Behaviors in Bharatpur Metropolitan City - Dahal, Niroj; Wagle, Sudip (Journal of Economics and Management, 2025)
This research explores the patterns and factors influencing alcohol consumption in Nepal, with a focus on demographic, social, and cultural variables. A total of 384 respondents participated in the survey, providing insights into gender, age, education, ethnicity, religion, and marital status, as well as their alcohol consumption behaviors. The findings reveal that cultural practices, personal preferences, and social pressures in shaping alcohol consumption behaviors during festive occasions. The findings contribute that AB is the most influential predictor, while FF has the least impact among the four. Overall, the results confirm that AB (alhocol brand), DE (demand of liquor), CE (caste/ethnicity), and FF (family/friends influence) all are significantly contribute to CL (consumption of liquor). These findings contribute to a deeper understanding of alcohol-related behaviors in the context of Nepal and provide valuable insights for policymakers and public health initiatives.